Synovial folds of the lateral atlantoaxial joints in dogs: a magnetic resonance, anatomic, and histologic study - Burg-Personnaz, J. B.; Kaessmeyer, S.; Forterre, F.; Precht, C.; Haenssgen, K. (Frontiers in Veterinary Science, 2025)
PurposeSynovial folds of the lateral atlantoaxial joints are well described normal anatomical structures in humans, which play a potential role in neck pain; however, scant information exists regarding these structures in dogs. The purpose of this study was to identify and describe atlantoaxial synovial folds in dogs using magnetic resonance imaging (MRI), gross anatomy and histological examination.MethodsSix client-owned dogs, euthanized for reasons unrelated to this study and without known disease in the craniocervical region, underwent postmortem MRI of the cranial cervical spine (3 Tesla, Siemens Magnetom Vida) using T2-weighted (T2w), T1-weighted (T1w), short tau inversion recovery (STIR), Dixon, and fat-suppressed volumetric interpolated breath-hold examination (VIBE) sequences. In five dogs the lateral atlantoaxial joints were gross anatomically dissected, while one of them underwent histological examination.ResultsFat-suppressed VIBE sequences provided optimal visualization of synovial folds within the atlantoaxial joints. Ventral synovial folds were discernible in all dogs by MRI and gross anatomical examination presenting as ventral synovial bulges extending into the joint space. While smaller dorsal synovial folds were identified by MRI only in 2 dogs, but by gross anatomical examination in all dogs. Light microscopy of the histological specimen confirmed that the folds were extensions of the joint capsule’s synovial membrane, which were mainly composed of vascularized connective and adipose tissue; and were covered by synovial cells.Discussion/conclusionSynovial folds are present in canine atlantoaxial joints free from known atlantoaxial disease. Dorsal and ventral folds could be visualized on post-mortem macroscopic and histological examinations. The larger ventral folds were consistently visualized using MRI with fat-suppressed VIBE sequences. The anatomical structure of the canine synovial folds suggests a similarity to humans, indicating that some conditions may analogously affect the synovial folds. Further investigations are warranted to elucidate the clinical relevance of these synovial folds in dogs.